Propriedades tecnológicas de madeiras tropicais submetidas à modificação térmica - Souza, Leonardo Vinícius de (2021)
To expand the range of tropical species commercially exploited some wood modification processes can be employed, such as thermal modification. This process aims to alter desirable characteristics in the wood through the action of high temperatures, especially color, which is an important factor for the acceptance of new species on the market. The present study aimed to evaluate the influence of thermal modification on the technological properties of the Amazonian woods Parkia pendula (Willd.) and Simarouba amara (Aubl.), comparing different means of heating the material under the same conditions of time and temperature. For this purpose, the woods were thermally modified in: electric oven with forced air circulation; modified with pre-treatment in autoclave, followed by treatment in electric oven after conditioning period; and by immersion in vegetable oil. All methods used a time of 3 hours at a temperature of 180°C. Physical properties (percent mass change; equilibrium moisture, bulk density, bulk swelling, and color), mechanical properties (Rockwell hardness strength, and modulus of elasticity and rupture), chemical properties (basic composition and Fourier transform infrared spectroscopy analyses), and biological properties (resistance to biodeterioration in the field and to natural weathering) were evaluated. The results showed that all the thermal modification methods used had an effect in improving the dimensional stability of the wood. Regarding mechanical properties, there was a reduction in Rockwell hardness and flexural strength, with greater preservation of strength in the vegetable oil treatment. The modification in oil was the only treatment that conferred increased resistance to biodeterioration in field tests. In the colorimetric analyses, darkened wood was observed after the thermal modification treatments, which had greater colorimetric stability than the wood without modification in the natural weathering test. In the basic chemical composition there were changes only for wood modified in vegetable oil, and in the FTIR analyses the peaks 3005cm-1, 2855cm-1 and 725 cm-1 were identified only in this treatment, being characteristic of triglycerides from soybean oil. Among the species, the Simarouba amara wood showed better response to the action of temperature on its technological properties, being necessary to carry out the process in Parkia pendula with temperature and time different from this study, to obtain the same intensity of modification.